Education, science and industry on the road to prevention, adaptation and mitigation of climate change - Vnukova, N. (ed.); Zhelnovach, G. (ed.) (Kharkiv National Automobile and Highway University, 2023)
The collective monograph was prepared by researchers from partner universities of the international ERASMUS+ project "Synergy of educational, scientific, managerial and industrial components for climate management and climate change prevention / CLIMAN" 619119-EPP-1-2020 -1-NL-EPPKA2- CBHE-JP. The publication highlights the results of own research on the general issues and origins of global climate change, sectoral issues of sustainable development, the implementation of natural based solutions, the application of innovative approaches to energy support for the development of transport, agriculture and waste disposal. The monograph is intended for a wide range of readers who are interested in the problems of global climate change, as well as ways of possible prevention, adaptation and mitigation of the climate change consequences.
Keywords: 504.062